Electrophoretic deposition of graphene on basalt fiber for composite applications - Mittal Garima (De Gruyter, 2021)
Basalt fiber (BF), because of having high strength-to-cost ratio, could be suitable for industrial applications replacing the carbon and glass fibers. However, the lack of surface functionality restricts its potential interfacial interactions with the reinforced matrix. Various surface modification approaches are used to tailor the surface properties of BFs such as coating nanomaterials and attaching chemical moieties. In this study, a successful deposition of graphene on basalt fabric was done using eco-friendly and simple electrophoretic deposition method. The confirmation of attached graphene oxide and graphene was done through the scanning electron microscope, Raman spectroscopy, and X-ray photoelectroscopy. Later, the effect of graphene coating on the thermal properties of BF was studied through thermogravimetric analysis and differential scanning calorimetry. Results show that the graphene was successfully coated on BF, and in the presence of graphene coating, the crystallization of BF delayed from 697 to 716°C because of the formation of a protective layer of graphene. Graphene-coated BF could be used further in fiber-reinforced composites to improve the interfacial interaction between the matrix and fiber.